Educational services for students with mental retardation in Kenya - Klarie, M.W. (International Journal of Special Education, 2006)
Research pertaining to issues on educational services for individuals with disabilities in developing countries is scarce. The purpose of this article is to two fold: first, to contribute to the already existing literature, and, secondly, and perhaps more importantly, to provide a foundation for prospective readers to better understand literature regarding educational services for students with mental retardation. This article guides the reader to understand the perspectives towards students with mental retardation, discusses the definition and causes of this condition, and discusses issues pertaining to the identification, assessment and evaluation of these students in Kenya. The core of the article contains a discussion of the various placement options available for this population along with the curriculum in operation in the various settings. Existing barriers to effectively serving this population in Kenya and in other developing countries is also discussed.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Children's reading comprehension and oral reading fluency in easy text - Spear-Swerling, Louise (Reading and Writing, 2006)
This study explored third-graders' oral reading fluency (ORF) in easy text in relation to their third- and fourth-grade reading comprehension. It also examined the children's performance on two different measures of text exposure, a self-report questionnaire and a title-recognition test. Although third-graders' ORF related significantly to their reading comprehension, oral language comprehension accounted for most of the variance in reading comprehension, whereas single word reading speed accounted for most of the variance in ORE Third-grade reading comprehension and ORF each predicted unique variance in children's scores on a fourth-grade state-mandated reading comprehension assessment. Scores on the self-report questionnaire correlated significantly with third-grade ORF and fourth-grade reading; the self-report accounted for reliable variance in ORF even with all of the other reading ability variables entered first. Results are consistent with the viewpoint that text exposure affects reading fluency. They also demonstrate that ORF is a valuable predictor of middle-elementary children's reading comprehension, even when the ORF measure employs very easy text in which children achieve near-perfect word accuracy.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-531-179-017-917 tex.type: [object Object]
Keywords: Comprehension; Fluency; Reading; Text exposure; dept.sed; peer-reviewed